Effects of farmers’ cultural practices on the weedy rice infestation and rice production - S.M. Rezaul Karim; Mashhor Mansor; Zainal Abidin (2012)
An on-farm trial was conducted at the Muda Agricultural Development Authority rice fields, Kedah, Peninsular Malaysia from November, 2003 to July, 2006 to study the impacts of farmers’ cultural practices on the weedy rice infestation and rice production. Five sample farmers (A, B, C, D and E) from five different sampling sites were selected on the basis of severity of weedy rice infestation on their fields in earlier seasons. Field observations and monitoring were carried out for collecting data and recording the agronomic practices done by the farmers from land preparation to harvesting of the crops. The number of weedy rice panicles per unit area was recorded from 50 sampling spots per plot using 1 × 1 m quadrat. Rice plants and the weedy rice within the quadrats were harvested. Data on grain yields and yield components were recorded. The collected data were analyzed statistically and mean differences in weed infestation were adjudged using standard error of means. Results revealed that the farmers used different rice varieties and applied different agronomic practices, which resulted in variable intensities of weedy rice infestations and production of variable rice grain yields. The farmers A and B, who followed transplanting and water seeding for crop establishment, applied pre-planting herbicides (2 to 3 times) during land preparation and used regular surveillance and monitoring (20 to 25 times) of their plots, had less weedy rice infestation (32.22 panicles/m2) and higher rice yields (6.70 to 8.88 t/ha). The farmers C, D and E, used wet direct seeding for crop establishment, applied no or less time of pre-planting herbicides (1 time) and had less field surveillance (10 to 15 times/season), had consequently a higher weedy rice panicle density (154.94 panicles/m2) and less rice yields (3.57 to 6.27 t/ha).